2012
DOI: 10.1111/j.1438-8677.2012.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salt stress and rhizobial inoculation on growth and nitrogen fixation of three peanut cultivars

Abstract: Increasing soil salinity represents a major constraint for agriculture in arid and semi-arid lands, where mineral nitrogen (N) deficiency is also a frequent characteristic of soils. Biological N fixation by legumes may constitute a sustainable alternative to chemical fertilisation in salinity-affected areas, provided that adapted cultivars and inoculants are available. Here, the performance of three peanut cultivars nodulated with two different rhizobial strains that differ in their salt tolerance was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 30 publications
(50 reference statements)
0
34
0
2
Order By: Relevance
“…The N 2 -fixing ability of groundnut is essential for sustainable yields and economic returns, especially in less developed countries [11]. A common problem encountered by groundnut farmers and growers of other legumes is the presence of low symbiotically efficient native microsymbionts in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…The N 2 -fixing ability of groundnut is essential for sustainable yields and economic returns, especially in less developed countries [11]. A common problem encountered by groundnut farmers and growers of other legumes is the presence of low symbiotically efficient native microsymbionts in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Salinity affects physical and chemical characteristics of the soil in the root zone, leading to deteriorated soil structure, reduced infiltration properties and nitrogen fixation, and increased pH, and thus to a reduction in plant yield and quality Rahnama et al 2011;Stefania et al 2012;El-Akhal et al 2013). Once soil salinity reaches the salt threshold, seed germination and vegetative plant growth will be reduced by different ratios (Boscaiu et al 2011;Razzaghi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Indirectly, rhizobia improve plant health by improving the self-defense of plant through induction of systemic resistant (Reddy, 2013) against harmful insects, pathogens, diseases and viruses (Huang and Erickson, 2007). Rhizobia have also been reported to improve the growth and yield of legumes (Ahmad et al, 2012;El-Akhal et al, 2013) and non-legumes (Afzal and Bano, 2008;Bano and Fatima, 2009) under salt stressed conditions. There are extensive reports of rhizobia for enhancement of number of primary roots, root proliferation, and plant growth promotion even under increased level of salinity (Naz et al, 2009;El-Akhal et al, 2013).…”
Section: Inoculation With Rhizobial Consortium For Improving the Growmentioning
confidence: 99%
“…Rhizobia have also been reported to improve the growth and yield of legumes (Ahmad et al, 2012;El-Akhal et al, 2013) and non-legumes (Afzal and Bano, 2008;Bano and Fatima, 2009) under salt stressed conditions. There are extensive reports of rhizobia for enhancement of number of primary roots, root proliferation, and plant growth promotion even under increased level of salinity (Naz et al, 2009;El-Akhal et al, 2013). Further, it has been demonstrated that coinoculation or multi-strain consortium of rhizobia with other PGPR or mycorrhizae gave better improvement than their alone inoculation under normal as well as salt stressed conditions (Yu et al, 2007;Afzal and Bano, 2008;Bano and Fatima, 2009).…”
Section: Inoculation With Rhizobial Consortium For Improving the Growmentioning
confidence: 99%